2006
DOI: 10.1007/s10995-006-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Healthcare: What Women Know and Believe

Abstract: Objectives: The objectives of this study were to determine if women realize the importance of optimizing their health prior to a pregnancy, whether the pregnancy is planned or not; and to evaluate their knowledge level and beliefs about preconception healthcare. Additionally, we sought to understand how and when women wanted to receive information on preconception health. Methods: A survey study was performed using consecutive patients presenting to primary care practices for an annual wellwoman exam. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 17 publications
9
95
1
2
Order By: Relevance
“…200 pregnant women were estimated as samples based on similar studies (7,10,13,18) and using the sample size estimation of Cochran (confidence level of 95%).…”
Section: Subjects and Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…200 pregnant women were estimated as samples based on similar studies (7,10,13,18) and using the sample size estimation of Cochran (confidence level of 95%).…”
Section: Subjects and Settingsmentioning
confidence: 99%
“…Frey in a study done on 499 women, referred to outpatient services clinic, found that women information-level of preconception risk factors affecting on the outcome of pregnancy was good, and most of them preferred to receive information from their doctor and/or gynecologist (10).…”
Section: Introductionmentioning
confidence: 99%
“…Riazi also found that although approximately 80% of pregnancies are planned, less than 10% of women use folic acid, even when they have a history giving birth to children with neural tube defects (18). In Frey and Files's study, deficiencies in women's knowledge about preconception risk factors that influence maternal and fetal health occur due to doctors' neglect of routine preconception health care (19). In the study by Wu conducted in England, 25% of women correctly used acid folic supplement before pregnancy (20).…”
Section: Introductionmentioning
confidence: 99%
“…Underlying these recommendations is an assumption that women will be aware and inclined to act before pregnancy-or can be educated to recognize and take action before pregnancy-to optimize health outcomes for themselves and their newborns. Yet little research has been conducted on preconception awareness or attitudes regarding birth outcomes (Frey & Files, 2006).Currently, it is not known whether women contemplating pregnancy believe that they can increase the likelihood of having a healthy baby through any actions of their own. This is an important topic because it is relevant to developing effective health education and social marketing campaigns to increase preparation for childbearing, and women would not be expected to modify their health behaviors if they did not believe that their actions could influence their birth outcomes.…”
mentioning
confidence: 99%